Um barulho na cidade: culturas juvenis e espaço urbano - Gadelha, Kaciano Barbosa (2007)
This dissertation deals with the relation between youth cultures and urban space in reference to the leisure spaces. The empirical reference area chosen was Noise 3D club, a night club in the area of Centro Cultural Dragão do Mar in Fortaleza. The author discusses the relations between musical styles and the symbolic appropriation forms of the city, with emphasis in the subjective aspect and in the temporal dynamic of youth cultures. The methodological procediments consisted in interviews, fieldwork (participant observation) and research in archives. The author concludes with a perception of the youth cultures in the contemporary city where the ephemeral character of the established social links is every more time present.